Fetal Atrial Flutter: Electrophysiology and Associations With Rhythms Involving an Accessory Pathway. Issue 6 (June 2016) - Wacker‐Gussmann, Annette; Strasburger, Janette F.; Srinivasan, Sharda; Cuneo, Bettina F.; Lutter, William; Wakai, Ronald T.
Abstract : Background: Atrial flutter (AFl) accounts for up to one third of all fetal tachyarrhythmias and can result in premature delivery, hydrops, and fetal death in 10% of cases; however, the electrophysiology of AFl in utero is virtually unstudied. Methods and Results: In this observational study, we reviewed 19 fetal magnetocardiography studies from 16 fetuses: 15 fetuses (21–38 weeks' gestation) referred with an echocardiographic diagnosis of AFl and 1 fetus (20 weeks' gestation) referred with a diagnosis of tachycardia that was shown by fetal magnetocardiography to have transient AFl in addition to atrioventricular reciprocating tachycardia. Thirteen fetuses showed AFl during the fetal magnetocardiography session, including 4 that presented prior to the third trimester. Five fetuses had incessant AFl; all but 1 of the others with AFl showed additional significant rhythms. Specifically, AFl showed a strong association with rhythms involving an accessory pathway: atrioventricular reciprocating tachycardia, blocked reentrant premature atrial contractions, and ventricular preexcitation. The observed initiations and terminations of AFl most often involved reentrant premature atrial contractions. Spontaneous termination of AFl showed AFl cycle length oscillations. Nine fetuses with 2:1 AFl also showed periods of 4:1 conduction or variable conduction that oscillated between 2:1 and 4:1; however, 3:1 AFl was relatively rare. Conclusions: Fetal AFl can occur as early as midgestation and is often accompanied by atrioventricular reciprocating tachycardia and other rhythms associated with an accessory pathway. The findings depict critical differences in the electrophysiology of AFl in the fetus versus the neonate.